Gastrointestinal bleeding after endoscopic mucosal resection in a case of Peutz–Jeghers syndrome with hypofibrinogenemia: A case report - Kakiuchi, Toshihiko; Takedomi, Hironobu; Akutagawa, Takashi; Tsuruoka, Nanae; Sakata, Yasuhisa; Matsuo, Muneaki (Frontiers in Pediatrics, 2022)
Backgroud: Peutz–Jegers syndrome (PJS) is an autosomal dominant hereditary disorder characterized by hamartomatous polyposis of the entire gastrointestinal tract. Fibrinogen (Fbg) is synthesized by the liver, and hypofibrinogenemia is often asymptomatic and manifests with bleeding after trauma or invasive surgical procedures. Here, we present a case of a pediatric patient with PJS and hypofibrinogenemia who manifested with gastrointestinal bleeding after endoscopic mucosal resection (EMR) of small intestinal polyps. Case Presentation: An 11-year-old boy with PJS was referred to our hospital. Since his mother was diagnosed with PJS, with black pigments being observed on his lips, mouth, and limbs, he underwent upper and lower gastrointestinal endoscopy at the age of 8 years at a previous hospital. EMR for duodenal polyp was performed, and the pathological findings were consistent with hamartoma. His Fbg level was 117 mg/dL at the time, with no post-bleeding being detected after EMR. The small intestine was not assessed at the prior facility and was left neglected for three years. At our hospital, small intestine fluoroscopy was performed and revealed a polyp in the jejunum, and abdominal computed tomography showed two polyps and intussusception. On double-balloon enteroscopy, the resected polyps were hamartoma with diameters of 20 and 30 mm. The patient’s Fbg level was 107 mg/dL. The day after EMR, he had melena and black stools. He was diagnosed with post-EMR bleeding and started to stop eating, and hemostatic agents were given. His hemoglobin level dropped to 9.2 g/dL the next day. Genetic testing for congenital Fbg deficiency revealed a heterozygous pathogenic variant in fibrinogen gamma chain Exon 10. Therefore, he was diagnosed with concurrent hypofibrinogenemia and PJS. Conclusion: To the best of our knowledge, this is the first reported case with concurrent PJS and hypofibrinogenemia. In patients with PJS, hypofibrinogenemia should be considered as one of the risk factors of postoperative bleeding during polypectomy, and appropriate prophylactic measures should be taken.